HOSPITALITY DURING THE CHALLENGES OF COVID-19 PANDEMICS - Kalenjuk, Bojana M; Smugovic, Stefan; Vujasinovic, Vesna; Lukic, Tamara (The Business of Tourism, 2021)
Sustainable business during the COVID-19 pandemic is one of the key topics in the hospitality and tourism industry with great popularization in scientific and research domains. Therefore, the focus of this research was on the experience of the management of catering facilities in R. Serbia. This qualitative research included collecting data on the operational and economic effects of the COVID-19 pandemic on the business of 17 catering facilities for the provision of food and beverage services. The research covered the period of work from April 2020 to April 2021, as the most specific for business survival, fighting the challenges of preventing the complete closing down, limited business, and a major re-orientation to delivery and counter sales. Interviews were conducted on the perception and attitudes of the management. The subject of this paper is the sustainability of hospitality during the challenges imposed by the pandemic. The task of the paper was to investigate the experiences of the owners, management, and chefs of various hospitality facilities for providing food and beverage services. The aim of the paper was to obtain data on crisis forecasting and actions taken to survive on the hospitality and tourism market.